Extra medullary myeloid cell tumor: A Case Report - Vemula, Sreenivas; Kasturi, Sumalatha; Maddi, Rahul Narayana; Margam, Vijay Mohan; Rendla, Santhosh Babu (Annals of Pathology and Laboratory Medicine, 2015)
Extra medullary myeloid cell tumors or granulocytic sarcomas or chloromas represents a localised tumor of myeloblasts or monoblasts infiltrating extramedullary sites. The term is used for any solid collection of leukemic cells in the extra haematopoietic sites. There have been reports of these tumors occurring concomitantly with, after, or rarely prior to the onset of leukemia. We present a case of a child presented with swelling in the right parotid region, which was diagnosed as chloroma on fine needle aspiration cytology. Further confirmation was done on peripheral blood and bone marrow evaluation.